THE INFLUENCE OF RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), CORPORATE SOCIAL RESPONSIBILITY (CSR), AND GOOD CORPORATE GOVERNANCE (GCG) ON STOCK PRICES IN COSMETIC AND HOUSEHOLD PRODUCTS COMPANIES - Dadi Kuswandi; Radi Sahara; Wiarsih Febriani; Devi Indira Handayani (Asosiasi Dosen Muda Indonesia, 2026)
Stock prices are an important indicator influencing investment decision-making. High stock prices reflect positive market perceptions of company performance and increase investor interest in investing. This study aims to analyze the influence of Return on Equity (ROE), Debt to Equity Ratio (DER), Corporate Social Responsibility (CSR), and Good Corporate Governance (GCG) on stock prices of cosmetic and household goods companies listed on the Indonesia Stock Exchange for the period 2019–2023. The sampling method used purposive sampling with a total of 6 companies or n = 36. The data used are secondary data in the form of annual financial statements and stock prices. The analytical method applied is multiple linear regression using IBM SPSS version 29. The results show that partially ROE and GCG have no significant effect on stock prices, DER has a significant negative effect, while CSR has a significant positive effect on stock prices. Simultaneously, ROE, DER, CSR, and GCG significantly affect stock prices. These findings highlight that leverage and corporate social responsibility play an important role in determining the market value of companies in the cosmetics and household goods industry.